The Emergence of Life From Chemical Origins to Synthetic Biology - Pier Luigi Luisi (Cambridge University Press, 2006)
"This book presents a systematic course discussing the successive stages of self-organization, emergence, self-replication, autopoiesis, synthetic compartments, and construction of cellular models, in order to demonstrate the spontaneous increase in complexity from inanimate matter to the first cellular life forms. A chapter is dedicated to each of these steps, using a number of synthetic and biological examples."--BOOK JACKET.